Examining the Relationships between Contraceptive Use and Childhood Mortality in Nigeria: A Multilevel Analysis - Raimi , Olatunde; Wegbom , Anthony Ike; Fagbamigbe , Adeniyi Francis; Olafusi , Oluwatosin Samson (American Journal of Biomedicine and Pharmacy, 2025)
Background Under-five mortality (U5M) in Nigeria continues to be high, while contraceptive use has not increased despite national and global commitments to improve reproductive health. This study examines the relationship between contraceptive use and childhood mortality. It further explores the direct and indirect pathways connecting contraceptive use to childhood mortality. Methods The research utilized data from the 2021 Nigeria Multiple Indicator Cluster Survey (MICS) that was carried out on a nationally representative sample of 38,768 women aged 15-49 years. Life table Stata ltable techniques were used to estimate child mortality rates from censored survival data, while logistic regression was employed to identify factors affecting contraceptive utilization. The Cox proportional hazards model was used to investigate the relationships between contraceptive use and under-five mortality. Results About two-thirds (62.2%) of the mothers were aged 25-34, 67.9% were rural residents, and 52.9% had given birth at home. The contraceptive prevalence rate (CPR) was 21.7%, while the under-five mortality rate was 103/1,000 live births. Mothers who used contraception had a slower rate of experiencing childhood mortality compared to non-user mothers (aHR = 0.812, CI: 0.674–0.981). Children whose mothers were aged 35+ (aHR = 0.305, CI: 0.109 – 0.854) had a slower rate of experiencing childhood mortality compared to mothers aged 15–24. Higher maternal education was associated with reduced mortality risk (aHR = 0.231, CI: 0.083–0.640). The moderation analysis revealed a greater effect of contraceptive use in reducing child mortality among educated mothers (β = -0.054, 95% CI: -0.115 to -0.0113). Conclusion The study highlights the relationship between maternal age, education, marriage, and place of residence and use of contraception and child survival in Nigeria. Therefore, low levels of contraceptive use remain a contributing factor to under-five mortality in Nigeria. Hence, targeted and context-defined reproductive health interventions are required to improve child survival outcomes in Nigeria.